The level’s changing of transforming growth factor β2 during canine retraction in non-growing age patient - Adianti Adianti; Ameta Primasari (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2015)
Background: Orthodontic tooth movement occurred as a result of alveolar bone remodeling and collagen due to mechanical load. This mechanical load applied to the tooth will exert a number of cytokine and growth factors. One of the growth factors that are often associated with orthodontic tooth movement is transforming growth factor-β(TGF-β). It has 3 isoforms, TGF-β1, TGF-β2, and TGF-β3. It has been known that in adult patient, tooth movement rate was slower. Purpose: The aim of this study was to investigate the changing level of TGF-β2 in non-growing patient due to mechanical load in canine retraction. Method: Gingival crevicular fluid from 6 subjects who undergo canine retraction was taken to investigate changing level of TGF-β2. Distal site of each upper canine served as an experimental tooth. The gingival crevicular fluid from experimental tooth was taken just prior to mechanical load, at 24h and 72h after mechanical load. Result: ELISA reader showed that level of TGF-β2 was decreasing during experiment time. Conclusion: It can be concluded that in non-growing patient, TGF-β2 has less role in alveolar bone resorption in orthodontic tooth movement.